Time-varying CAPM and its Applicability in Cost of Equity Determination - Glova, Jozef (Procedia economics and finance, 2015)
The current paper explores CAPM in its dynamic time-varying form generally applicable in determination of equity costs within business valuation process. We briefly describe the literature on the CAPM and general index model specifying risk premium and equity costs determination. Our short discussion of the published literature suggests that while the CAPM is still popular with the professional practice, its effectiveness for risk premium determination is limited. So in the next part we shortly describe the applicability of the time-varying CAPM as an augmented approach to the traditional CAPM form. To illustrate applicability of the model we employ this augmented concept by incorporating only unexpected changes in the autoregressive time series models in a specified company Dell Inc. In the final part we discuss achieved results and their possible applicability in equity risk premium determination. Distribution fitting and simulation techniques have been also used to provide more viable results of equity costs.